The digital horizon in colorectal cancer surgery: A narrative review - Atanu Pal (Laparoscopic, Endoscopic and Robotic Surgery)
Digital surgery is being increasingly used in phraseology and clinical application, driven by the advancing tide of technology. Its scope in treating patients with colorectal cancer is reviewed. A search was performed to include a breadth of digital technologies, including virtual reality (VR), augmented reality (AR), artificial intelligence (AI), mobile health, and simulation. Many digital roles were identified in the 60 studies included. These were clinician-facing or patient-facing throughout the patient’s journey (screening, preoperative, intraoperative, postoperative) and involved the broader team (trainees, oncology, pathology). Colorectal cancer screening was improved via the use of digital technology, including virtual health assistants. Preoperative patient-facing VR enhances consent and reduces perioperative anxiety. For surgeons, enhanced awareness of vascular and visceral anatomy relative to the tumour helped with surgical planning, with the emerging concepts of ‘virtual colectomy’ and ‘digital clone’. Pathologically, AI more accurately predicts lymph node metastasis following endoscopic polyp cancer excision, thus reducing over-treatment with surgery, and assesses the response to neoadjuvant treatment to guide selective surgery. Intraoperatively, AI facilitates real-time detection of anatomical landmarks, including autonomic nerves, ureters, and areolar tissue, to indicate the dissection plane. These intraoperative studies lacked a control group and outcome reporting (intraoperative, clinical, oncological, or functional), highlighting that this technology requires further development and study. There is a paucity of evidence regarding AR, such as intraoperative holographic overlay. Postoperative patient-facing digital technology can promote enhanced recovery, improve physical activity, and reduce sick-role maladaptation. For clinicians, AI can predict the short-term (complications) and long-term (survival) patient prognosis. VR could play an increasing role in training, with some evidence from validated virtual curricula. In summary, digital surgery has potential applications throughout the patient journey and along the virtuality continuum, showing advantages over conventional approaches in the preoperative and postoperative phases. Intraoperative, AI and AR methods have not yet been shown to have clinically significant advantages. As its scope grows, there are emerging implications for training, regulation, and ethics.